Analisis Perbedaan Kualitas Laba Sebelum dan Sesudah Penerapan PSAK 116 pada Perusahaan Transportasi - Fiyona Kacaribu (Prosiding, 2026)
This study aims to analyze the differences in earnings quality before and after the implementation of PSAK 116 in transportation services sub-sector companies listed on the Indonesia Stock Exchange. PSAK 116 is an accounting standard that regulates the recognition, measurement, and presentation of lease transactions by requiring the recognition of right-of-use assets and lease liabilities in financial statements. The research method used is a quantitative approach with a comparative method using secondary data in the form of the company's annual financial statements for the period 2018–2023. The research sample was selected using a purposive sampling technique to obtain 12 companies that met the research criteria. Earnings quality was measured using discretionary accruals with the Modified Jones model. Data analysis was carried out using a normality test and hypothesis testing using a difference test for two paired samples. The results showed that there was no significant difference in earnings quality before and after the implementation of PSAK 116. Thus, the implementation of PSAK 116 has not shown a material impact on earnings quality in the transportation services sub-sector companies that were the object of the study.